The social media effect: how K-pop fans are driven by social influence and community norms - Azmi Murad, Masrah Azrifah; Nasharuddin, Nurul Amelina; Roslan, Muhammad Amirul Asyraaf (Universiti Teknologi MARA (UiTM), 2024)
This study investigates the impact of Social Influence on the Behavioural Intention to use social media among K-pop fans, utilising a qualitative approach grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT). Social media has become an integral platform for K-pop fans, fostering interaction, content sharing, and community building. We focused on Social Influence, one of UTAUT's key constructs, to understand how peer pressure, community norms, and influencer endorsements drive social media engagement in this context. Data were collected through systematic observations of social media activities and posts by prominent K-pop fan accounts. The analysis revealed that peer pressure significantly motivates fans to participate in activities such as voting, streaming, and sharing content, driven by the desire to conform to group expectations. Community norms were evident in coordinated efforts to achieve collective goals, such as streaming targets, which reinforce shared values and behaviours. Influencer endorsements from well-known fan accounts further amplified participation, as followers were more likely to engage in actions promoted by trusted figures. These findings provide significant insights into Social Influences critical role in technology adoption within fan-driven communities. The study offers practical implications for marketers and social media platforms to leverage Social Influence in designing targeted engagement strategies. Limitations include the focus on publicly available content, which may not capture private interactions, and the subjective interpretation of social media posts. Future research should explore longitudinal and comparative studies to deepen understanding of Social Influence in various fan communities.